The Role of Consumption in the Economy – An Evolution of the Ideas from Cantillon to Keynes - Ivanova, Tatiana (Research Papers, 2020)
The article is a critical review, systematization, comparison and summary of the views on the role of the consumption for the dynamics of the economy from Cantillon to Keynes. Emphasis is placed on the alternatives of ideas, explained by the different assumptions and suggestions of the authors, and the changes in the economic conjuncture. In the context of the global crisis, the debate is revived, and the increasing demand is again one of the main opportunities for the implementation of the macroeconomic policy.